Numerical Modeling for Novel Solar Air Heater Utilizing Wax Paraffin-PCM - Salih, Salah M.; Najim, Saleh E.; Jalil, Jalal M. (Basrah Journal for Engineering Sciences, 2019)
A mathematical model to analysis three–dimensional forced convection turbulent flow in a novel solar air heater integrated with multiple rectangular capsules filled by paraffin wax-based on phase change material PCM was implemented. The investigations were performed under three airflow speed of (0.6, 1.2, and 1.8) kg/min and average solar flux of 625 W/m 2 . The results revealed that the delaying melting time and also lower the melting temperature of PCM by increasing airflow speed during the charging process. As well as, the freezing period is dependent on the airflow speed by inverse relation. Also, the data results represent that the useful energy rate and thermal storage efficiency were a strong dependence on the airflow speed. Moreover, it can be detected that the optimal freezing time and the air temperature rise of the heater were reached about 210 minutes with (12 – 1.5 °C), 150 minutes with (7.5 – 1.4°C), and 120 minutes with (5.5 – 1.5 °C), at airflow speed of 0.6, 1.2, and 1.8 kg/min, respectively, which can be used at night to supply some applications by thermal energy such as heating buildings and drying agricultural crops.